2008
DOI: 10.1074/jbc.m803544200
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1 Cooperates with C/EBPα in the Inhibition of Liver Proliferation in Old Mice

Abstract: Epigenetic control of liver proliferation involves cooperation between transcription factors and chromatin-remodeling proteins. In this work, we found that the levels of HDAC1 (histone deacetylase 1) are increased in quiescent livers of old mice. The elevation of HDAC1 in liver is mediated by the RNA-binding protein CUGBP1. We found that the age-associated CUGBP1-eIF2 complex binds to the 5 region of HDAC1 mRNA and increases translation of HDAC1 in the liver. Further analyses showed that CUGBP1 also increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
98
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 28 publications
1
98
0
Order By: Relevance
“…Therefore, the S193D mice represent a powerful animal model for the investigations of the responses of livers of aged mice to drug treatments. Another member of C/EBP family, C/EBP␤, is similar to C/EBP␣ and is involved in the regulation of chromatin structure of hepatocytes through interactions with HDAC1 (16,17). It has been shown that the C/EBP␤-HDAC1 complexes are abundant in livers of old mice and repress SIRT1 (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the S193D mice represent a powerful animal model for the investigations of the responses of livers of aged mice to drug treatments. Another member of C/EBP family, C/EBP␤, is similar to C/EBP␣ and is involved in the regulation of chromatin structure of hepatocytes through interactions with HDAC1 (16,17). It has been shown that the C/EBP␤-HDAC1 complexes are abundant in livers of old mice and repress SIRT1 (18).…”
mentioning
confidence: 99%
“…The formation of C/EBP␤-HDAC1 complexes is mainly controlled by the RNA-binding protein CUGBP1 (14). CUGBP1 increases translation of HDAC1 and two isoforms of C/EBP␤: C/EBP␤-LAP and C/EBP␤-LIP (16,17,19). A truncated isoform of C/EBP␤-LIP lacks activation domains and functions as a dominant-negative molecule by inhibiting activities of fulllength C/EBP␣ and C/EBP␤ proteins (20,21).…”
mentioning
confidence: 99%
“…Interactions between C/EBP and E2F also play important roles during senescence. Indeed, C/EBPα and HDAC1 are recruited to hepatic DNA from older, but not young, mice (Wang et al, 2008). Recruitment of these two factors is accompanied by decreased transcription of E2F target genes.…”
Section: C/ebpmentioning
confidence: 99%
“…CELF1-HDAC1-C/EBPbeta pathway is activated in young rat liver cells and in human tumor liver samples suggesting that CELF1-HDAC1-C/EBPbeta complexes are involved in the development of liver tumors [162], [163]. The inhibition of the ubiquitin-dependent proteasome system (UPS) via specific drugs (such as Bortezomib) is one type of approach used to combat cancer [164].…”
Section: The Gre/celf1 Posttranscriptional Network In Human Diseasesmentioning
confidence: 99%